Financial Reporting Quality and Ownership Structure in Companies Listed on The Warsaw Stock Exchange - Piasecki , Marcin (Studia Oeconomica Posnaniensia, 2018)
The article investigates whether there is a relationship between financial reporting quality and ownership structure in companies listed on the Warsaw Stock Exchange. Panel regression including 88 companies with their financial data from 2006-2012 was conducted to examine the relationship. The results indicate that the size of a company has a considerable impact on the relationship between financial reporting quality and ownership structure. This relationship is negative - as the size of a company increases, manager influence on financial statements tends to decrease.